Assessing the impact of cluster farming on multidimensional food security: Evidence from rural households in Northwestern Ethiopia - Getachew E. Gidelew; Bamlaku A. Alemu; Koyachew E. Kassie (Journal of Agriculture and Food Research)
This study investigates the impact of cluster farming on multidimensional food security in Northwestern Ethiopia. Data were collected from 421 randomly surveyed households. The Entropy Balancing Estimation (EBE) and Augmented Inverse Probability Weight (AIPW) estimators were used for data analysis. As a measure of food security, the study employs four dimensions—quantity, quality, acceptability, and stability—along with the multidimensional food security status. Regardless of a slight variation in the magnitude of their effect, the two models’ results are consistent. Specifically, except for the quality dimension, which is not statistically significant, our result suggests cluster farming significantly improves the remaining three dimensions of food security. The binary outcome analysis also indicates that households involved in cluster farming are more likely to fall into multidimensional food security status. Overall, we find a positive relationship between cluster farming and multidimensional food security. Thus, spreading this farming approach to a wider farming community is desirable to enhance food security but it should be based on awareness creation and farmers' willingness.